Risk Factors of Delayed Graft Function in Patients with Kidney Transplantation - Oyunpurev Erdenechimeg; Tuvshinbayar Javzan; Uugan-Erdene Amarbold; Od-Erdene Lkhaakhuu; Kishgee Tseren; Nyamsuren Davaajav; Bayan-Undur Dagvadorj; Erdenesaikhan Mendbayar; Ganbold Gantulga; Javkhlantugs Dondog; Zolzaya Nyamsuren; Sarantsetseg Jigjidsuren; et al. (Central Asian Journal of Medical Sciences, 2025)
Objective: In Mongolia, since 2006, kidney transplantation has been performed regularly, with more than 400 people having undergone this surgery. This preliminary study aimed to investigate the incidence of delayed graft function after kidney transplantation in Mongolia and to identify the associated risk factors. Methods: This study used a retrospective approach, gathering data from monitoring records. We applied the Student t-test, one-way ANOVA, Wilcoxon rank sum test, Kruskal-Wallis rank test, Spearman correlation, multivariate linear regression, and logistic regression. Results: Of the 268 recipients, 198(74.44%) were male. There were 14 total cases of DGF, of which 13 were transplanted from brain-dead donors. Postoperative urine outcome decreases by 120 mL for a 1-year increase in donor age (b = -120, p= 0.033). A 1-minute increase in cold ischemia time results in a 20-mL decrease in urine output (b = -20, p= 0.002). Donor age>40 increased the risk by 1.2 times (OR=1.2, p= 0.05), and brain-dead donor increased the risk by 19.37 times (OR=19.37, p= 0.0001), while recipient age<35 reduced the risk by 5 times (OR=0.2, p= 0.039). Conclusion: Our study found that risk factors such as older donor and recipient age, prolonged cold and warm ischemia times, and brain-dead donor status were associated with an increased risk of delayed graft function.